PENATALAKSANAAN FISIOTERAPI PADA KONDISI CERVICAL ROOT SYNDROM ET CAUSA SPONDYLOSIS CERVICAL DENGAN MENGGUNAKAN MODALITAS TRAKSI CERVICAL,INFRA RED DAN TERAPI LATIHAN DI RSUD BENDAN KOTA PEKALONGAN - Dyah Sulistyowati; Rendra Gita Aulia M.H (LPPM Universitas Pekalongan, 2014)
Cervical root syndrome et causa spondylosis cervical is a condition caused by degeneration of factors that occur in the discus intervertebral C1-C7, due to the emphasis on the spinal cord in the neck. Problems on cervical spondylosis is often the case, namely: pain, limitation of motion, muscle spasm, and decreased functional ability. To provide an effective and efficient treatment, then was examined for pain, range of motion, muscle spasm and functional ability. In addressing this problem given modalities such as cervical traction, infrared and exercise therapy. Having given action for 6 times with VAS can be obtained significant results, namely: pain still 1 cm to 0 cm, tenderness 8 cm to 5 cm, 7 cm motion pain into 4 cm, LGS on neck S=40o-0o-40o be S=40o-0o-40o, T=30o-0o-30o to T=40o-0o-40o, R=40o-0o-40o into R=45o-0o-45o muscle spasm 3 becomes 2, functional ability on neck disability index from 20 to 16.